2011
DOI: 10.3858/emm.2011.43.5.030
|View full text |Cite
|
Sign up to set email alerts
|

PAUF promotes adhesiveness of pancreatic cancer cells by modulating focal adhesion kinase

Abstract: Pancreatic cancer is a notorious disease with a poor prognosis and low survival rates, which is due to limited advances in understanding of the molecular mechanism and inadequate development of effective treatment options over the decades. In previous studies, we demonstrated that a novel soluble protein named pancreatic adenocarcinoma up-regulated factor (PAUF) acts on tumor and immune cells and plays an important role in metastasis and progression of pancreatic cancer. Here we show that PAUF promotes adhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…PAUF also plays important roles in cancer progression, including cell proliferation, adhesion, migration and invasion (20)(21)(22)(23). In our present study, we detected the expression levels of PAUF in 48 cases of CRC by using real-time RT-PCR.…”
Section: Discussionmentioning
confidence: 85%
“…PAUF also plays important roles in cancer progression, including cell proliferation, adhesion, migration and invasion (20)(21)(22)(23). In our present study, we detected the expression levels of PAUF in 48 cases of CRC by using real-time RT-PCR.…”
Section: Discussionmentioning
confidence: 85%
“…Sequence homology indicates that WGA16 is closer to human and pig ZG16b than human ZG16p. A recent study (66) reported that ZG16b facilitates tumor growth and metastasis through enhancing cell adhesiveness by regulating interactions between tumor cells and extracellular matrix molecules.…”
Section: Discussionmentioning
confidence: 99%
“…1E). Moreover C-X-C chemokine receptor 4 (CXCR4) expression, induced by PAUF and proposed to be associated with enhanced metastasis of carcinoma cells [20], was also reduced by PMAb83. These data indicate that PMAb83 can effectively impair in vivo tumor progression and metastasis by specifically targeting PAUF.…”
Section: Pmab83 Impedes Pancreatic Tumor Cell Progression and Metastamentioning
confidence: 99%
“…Based on our previous observations that PAUF strengthens the cancer-associated traits of PDAC cells [19,20], we next explored the effects of PMAb83 at the cellular and molecular levels. dose-dependent manner ( Fig.…”
Section: Pmab83 Attenuates the Tumorigenic Traits Of Pancreatic Carcimentioning
confidence: 99%
See 1 more Smart Citation